New economic patterns in Czechoslovakia : impact of growth, planning, and the market - Feiwel, George R. (New York: Praeger, 1968)
This is a study on the sources of growth and retrogression and on changes in working arrangements of the East European economies on which the Soviet model of development and the planning system were imposed after World War II. This study focuses on Czechoslovakia.
Bibliographical references included in "Notes" (p. 511-589)
lje 10/05/2018
Loans
Keywords: Czechoslovakia